Social Criticism in the Lyrics of Songs Entitled Tousaku, Shisouhan, and Hirutonbi by Yorushika - Zahwa Fahmi, Muhammad Alvin; Wahyuddin, Zida (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Social criticism is used to convey criticism that is communicated about a phenomenon that occurs in society. Social criticism acts when there is disapproval of other people's actions that are not in accordance with applicable rules, norms and values. Social criticism is conveyed directly or indirectly which can be voiced through various critical media. The lyrics of songs entitled Tousaku, Shisouhan, and Hirutonbi by Yorushika are one of the many media that contain elements of conveying social criticism. This research uses a qualitative descriptive method with a literary sociology approach to determine the relationship between literary works and phenomena that occur in society in order to foster elements of social criticism. The data from this research is in the form of social criticism identified through song lyrics. The data source for this research is the lyrics of Yorushika's songs entitled Tousaku, Shisouhan, and Hirutonbi. The aim of this research is to find out and describe social criticism and forms of conveying social criticism in the lyrics of Yorushika's songs entitled Tousaku, Shisouhan, and Hirutonbi. From the analysis, six data findings were found that contained elements of social criticism regarding moral, economic and cultural issues. Direct and indirect forms of conveying criticism are also found in the lyrics of songs entitled Tousaku, Shisouhan, and Hirutonbi by Yorushika.